Radix entomolaris: A case report with cone-beam computed tomography evaluation - Shafia Sarfi; Dildeep Bali (Wolters Kluwer Medknow Publications, 2017)
The purpose of this article is to draw the correlation between the morphology of the right and left radix entomoralis (RE) in a bilateral case using CBCT. In this report a case involving root canal treatment of both the mandibular molars (36 & 46) is presented. A correlation between the morphology of the two is drawn using CBCT. During root canal treatment of 46 the presence of RE was identified clinically and then radiographically. Following which, 36 was treated and similar morphologic variation was seen. A CBCT was performed after obturation of both the teeth was completed in order to analyse and compare the morphologic variation and similarity. The morphology of both the radices was found to be similar. Anatomic variations can occur in any tooth, therefore careful clinical and radiographic examination is compulsory for successful outcome. This report describes the similarity of tooth root anatomy in a patient with bilateral RE and hence its clinical implication.